Cost-effectiveness of adding oseltamivir to primary care for influenza-like-illness: economic evaluation alongside the randomised controlled ALIC4E trial in 15 European countries - Li, Xiao; Bilcke, Joke; van der Velden, Alike W; Bruyndonckx, Robin; Coenen, Samuel; Bongard, Emily; de Paor, Muirrean; Chlabicz, Slawomir; Godycki-Cwirko, Maciek; Francis, Nick; Aabenhus, Rune; Bucher, Heiner C; et al. (The European journal of health economics, 2023)
BACKGROUND: Oseltamivir is usually not often prescribed (or reimbursed) for non-high-risk patients consulting for influenza-like-illness (ILI) in primary care in Europe. We aimed to evaluate the cost-effectiveness of adding oseltamivir to usual primary care in adults/adolescents (13 years +) and children with ILI during seasonal influenza epidemics, using data collected in an open-label, multi-season, randomised controlled trial of oseltamivir in 15 European countries. METHODS: Direct and indirect cost estimates were based on patient reported resource use and official country-specific unit costs. Health-Related Quality of Life was assessed by EQ-5D questionnaires. Costs and quality adjusted life-years (QALY) were bootstrapped (N = 10,000) to estimate incremental cost-effectiveness ratios (ICER), from both the healthcare payers' and the societal perspectives, with uncertainty expressed through probabilistic sensitivity analysis and expected value for perfect information (EVPI) analysis. Additionally, scenario (self-reported spending), comorbidities subgroup and country-specific analyses were performed. RESULTS: The healthcare payers' expected ICERs of oseltamivir were €22,459 per QALY gained in adults/adolescents and €13,001 in children. From the societal perspective, oseltamivir was cost-saving in adults/adolescents, but the ICER is €8,344 in children. Large uncertainties were observed in subgroups with comorbidities, especially for children. The expected ICERs and extent of decision uncertainty varied between countries (EVPI ranged €1-€35 per patient). CONCLUSION: Adding oseltamivir to primary usual care in Europe is likely to be cost-effective for treating adults/adolescents and children with ILI from the healthcare payers' perspective (if willingness-to-pay per QALY gained > €22,459) and cost-saving in adults/adolescents from a societal perspective.
Keywords: Humans; primární zdravotní péče; dítě; Primary Health Care; Quality of Life; Influenza, Human; Child; Oseltamivir; oseltamivir; dospělí; Virus Diseases; virové nemoci; lidé; Europe; kvalita života; Quality-Adjusted Life Years; Adult; chřipka lidská; analýza nákladů a výnosů; Adolescent; kvalitativně upravené roky života; Cost-Benefit Analysis; Evropa; mladiství